Housing Challenges Among Young People in Greater Kuala Lumpur (GKL), Malaysia - Yaacob, Mahazril 'Aini; Bakar, Siti Hajar Abu; Wan Abd Aziz, Wan Nor Azriyati (American Scientific Publishers, 2017)
The need for quality housing is a dream of the younger generation because housing is a basic need in their transition to living independently. The transition to independent living usually occurs due to job demand, family formation, educational reasons and entry to homeownership. Nevertheless, this group of people faces several housing issues, such as failure to access their preferred housing tenure, difficulty purchasing their own home, and inability to access rental housing. Most of them, especially those residing in urban areas have encountered difficulties in attaining independent housing of their choice due to various problems. They have failed to access adequate and affordable homes which has resulted them renting private residences, sharing accommodation with their friends, continuing to reside in their parental homes or, even worse, becoming homeless. A survey, involving about 396 respondents, was carried out to investigate the challenges faced by the younger generation in their pursuit of adequate housing which in turn helps them achieve independent living. The discussion of the challenges highlighted offers possible strategies to resolve the housing issues haunting this generation.